Professional success as a component of personal psychological well-being - LYTOVCHENKO, Nina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . The relevance of the study of the problems of psychological well-being of the individual is due to extreme circumstances in the development of human society, which are, for example, the COVID pandemic, local wars, as well as sufficiently high requirements for the professional achievements of the individual in society, which affect the current trends of changes in social interaction. The purpose of the study is to study personal predictors of achieving professional success as a component of psychological well-being.M e t h o d s . The research used theoretical methods (analysis, comparison, generalization, systematization, empirical, namely: 1) The scales of psychological well-being by K. Riff. 2) Optimism and Activity Scale (AOS) by N. Vodopyanova, M. Shtern; 3) SAMOAL questionnaire (A. V. Lazukin, adaptation by N. F. Kalinaya), as well as statistical: correlation analysis according to K. Pearson (r), statistical criterion of significance of difference (Mann – Whitney U-criterion).R e s u l t s . It was found that professionally successful subjects are highly active in combination with adaptability to new situations, internal locus of control and high sociability. A positive worldview is an important attribute of psychological health and well-being, characteristic of professionally successful people. Optimism as a positive life attitude combined with activity (energy) is a psychological resource of individual resistance to professional and life stresses. Reliably significant differences between the groups of professionally successful subjects and the control sample were determined on the scale "orientation in time" and "spontaneity".C o n c l u s i o n s . It is substantiated that the professionally successful researched feelings of subjective well-being are associated with reliable social ties, good health and satisfaction with the activities they perform. It is proved that for the subjects of the control sample, the subjective feeling of well-being is primarily associated with the absence of tension in life, and self-actualization is an important aspect of life creation for professionally successful people. It is argued that professionally successful subjects are satisfied with everyday activities, understand the importance of living here and now, are open to new ideas, opportunities and impressions.
Keywords: psychological well-being; professional success; subjective well-being; optimism; self-actualization of the individual